Investigation of surface roughness in milling with air and conventional cooling method - Tosun, Nihat; Kuru, Can; Altintaş, Emin; ErdiN, Olcayto Erdem (My University, 2010)
In this study, the surface roughness of workpiece was experimentally investigated in milling of AA7075-T6 by using conventional and air cooling methods. The air used in machining with air cooling method was delivered to the cutting zone tool with two different flow rates (20 ve 40 m/s). The mixture of boron oil and water was used as the cutting fluid in the conventional cooling method. The experiments were performed with different cutting tools (HSS, carbide), spindle speeds (780, 1330, 2440 rpm) and feed rates (20, 40, 80 mm/min). It is determined in experiments that the surface roughness was increased when feed rate was increased but the surface roughness was decreased when the spindle speed was increased. In addition, the surface roughness results obtained by using carbide tools in the experiments are better than that of HSS tools and the surface roughness results obtained by using the air cooling method are better than that of conventional cooling method.
Hava ve geleneksel so?utma yöntemi? i?le frezelemede yüzey pürüzlülü?ünün i?ncelenmesi?
Keywords: Air cooling; Conventional cooling; Milling; Surface roughness